Evaluation of in vitro biological activities: antioxidant; anti-inflammatory; anti-cholinesterase; anti- xanthine oxidase, anti-superoxyde dismutase, anti-Î±-glucosidase and cytotoxic of 19 bioflavonoids - Khelifi, Imen; Hayouni, El Akrem; Cazaux, Sylvie; Ksouri, Riadh; Bouajila, Jalloul (Cellular and Molecular Biology, 2020)
Pure compounds belonging to phenolic family were studied for their biological potential such as 5,8-dihydroxy-1,4-naphthoquinone (M1), rutin hydrate (M2), 2,3-dichloro-5,8-dihydroxy-1,4-naphthoquinone (M3), taxifolin (M4), myricetin (M5), plumbagin (M6), silibinin (M7), dihydromyricetin (M8), shikonin (M9), quercetin 3-Î²-D-glucoside (M10), (±)-taxifolin hydrate (M11), cardamonin (M12),(âˆ’)-epicatechin (M13), 9-chloro-10-hydroxy-anthracene-1,4-dione (M14), 9-chloro-10-hydroxy-2,3-dimethyl-anthracene-1,4-dione (M15), 2-chloro-3-(2-hydroxy-5-methylanilino)-1,4-naphthoquinone (M16), 2-chloro-3-(4-hydroxy-phenylamino)-(1,4) naphthoquinone (M17), 2-chloro-3-(3,5-di-tert-butyl-4-hydroxy-phenyl)-(1,4)-naphtoquinone (M18), and myricitrin dihydrate (M19). These molecules were chosen based on two reasons; the limited or total absence of their exploitation in several studied activities and the use of other tests for the same activity. The evaluation of the in vitro anti-acetyl-cholinesterase (AChE), anti-5-lipoxygenase (5-LOX), anti-xanthine oxidase (XOD), anti-alpha glucosidase, anti-superoxide dismutase (SOD), anti-oxidant (DPPH (1, 1-diphenyl-2-picrylhydrazyl) and ABTS (2, 2- azinobis-3-ethylbenzothiazoline-6-sulphonate)), and anticancer activities of mentioned 19 molecules was explored during this work. M3, M14, M15, M16, M17, M18, M19 were exploited for the first time for such purposes. Tested compounds were shown to have interesting radical scavenging abilities against DPPH radicals, and the highest molecules among them were M19 and M5 (IC50 = 12.0 and 15.5 µM, respectively), and M4, M19 and M2 against ABTS (IC50= 1.9, 4.3 and 4.3 µM, respectively). Moreover, the majority of products showed very important cytotoxic activity since IC50 values were ranging between (IC50= 0.2 µM (M1) and 79 µM (M8)) against HCT116 cell line, and values of IC50= 0.2 µM for M1 against MCF7 cell line. All new molecules (non studied before) were shown to have great cytotoxic effect against both cancer cell lines. Furthermore, molecule M5 was shown to have anti-inflammatory potential via the inhibition of 5-LOX enzyme (65% at 100 µM). In addition, M19 showed important anti XOD activity with 47% of inhibition at 100 µM. Also, it has been found that compound M3 had the best anti alpha glucosidase activity with 43.8 % of inhibition at 100 µM, the highest anti-AChE effect (IC50= 14.5 µM), and the best effect towards SOD (IC50= 10.0 µM). A structure-activity relationship study was also performed.